ANALISIS KURIKULUM EKONOMI SYARIAH PADA PROGRAM STUDI PERBANKAN SYARIAH DAN PROGRAM STUDI MANAJEMEN BISNIS SYARIAH FAKULTAS EKONOMI DAN BISNIS ISLAM DI INSTITUT AGAMA ISLAM SAHID BOGOR - Lelih Amaliah; Misno; Ujang Buchori Muslim (Institut Agama Islam Sahid Bogor, 2022)
This research was conducted to find out how the Islamic economics curriculum is in the Islamic banking and Islamic business management study programs, to find out what are the learning materials and learning plans of Islamic economics in the Islamic banking and Islamic business management study programs and then to analyze the implementation of the applied curriculum. This research uses descriptive qualitative research. The results and discussion of these lecturer competencies have supported the curriculum competencies of the Islamic banking and Islamic business management study programs and in accordance with the vision and mission of each study program, there has been an update of the old curriculum to the new curriculum for several relevant reasons, semester credit units taken from semester one up to the eighth semester totaling one hundred and forty eight semester credit units, sharia economics aims to carry out humane economic activities, from the alumni data the researchers found that the curriculum was actually good but not successful because there were many graduate or alumni professions who were not entrepreneurs so there was a need for a re-review This curriculum is so that the curriculum is made in such a way that it can produce entrepreneurs, at least students who have an entrepreneurial spirit. Lecturers Need to improve Education and teaching, research and community service and must be supported by facilities and infrastructure that support the achievement of curriculum competencies. Libraries as a science need books, research journals, modules that are up-to-date and balanced with the competencies needed by each study program